2017
DOI: 10.4149/bll_2017_045
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of diltiazem and tadalafil on shock wave-induced kidney injury in rats

Abstract: BACKGROUND: We aimed to compare the protective effects of tadalafi l and diltiazem on renal histology after ischemia and reperfusion injury in a rat model of shock wave lithotripsy. METHODS: A total of 40 adult, male Sprague-Dawley rats were randomized into four groups as follows; control group (group C), group S (SWL + nephrectomy), group T (SWL + tadalafi l given before nephrectomy) and group D (SWL + diltiazem given before nephrectomy). Both kidneys were evaluated regarding tubular damage, peritubular fi br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the study of Sugimoto et al [ 17 ] investigating the effect of tadalafil at a dose of 10 mg/kg for 30 days in the rat prostate in a nonbacterial prostatitis model, it was reported that tadalafil showed anti-inflammatory and stromal anti-proliferative effects at this dose and time. In addition these, in the study of Özmerdiven et al, it was reported that tadalafil had positive effects on post-ESWL renal damage [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Sugimoto et al [ 17 ] investigating the effect of tadalafil at a dose of 10 mg/kg for 30 days in the rat prostate in a nonbacterial prostatitis model, it was reported that tadalafil showed anti-inflammatory and stromal anti-proliferative effects at this dose and time. In addition these, in the study of Özmerdiven et al, it was reported that tadalafil had positive effects on post-ESWL renal damage [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is possible to find many studies using tadalafil as an exogenous antioxidant to reduce various organ damage due to ROS. However, these studies differ from each other in terms of their results [ 1 , 15 18 ]. With this study model, we investigated the effects of hyperoxia on the rat kidneys and whether tadalafil has an effect to reduce this damage, to shed some light on this issue.…”
Section: Introductionmentioning
confidence: 99%